Caracterização estrutural de uma lectina nociceptiva obtida de sementes da espécie Platypodium elegans VOG - Silva, Ivanice Bezerra da (2017)
A native lectin (nPELa), purified from seeds of the species Platypodium elegans, Dalbergieae tribes, was crystallized and structurally characterized by methodologies such as X-ray diffraction crystallography and bioinformatics tools. The obtained crystals (of orthorhombic type) were diffracted with quality and nPELa structure was solved with excellence through molecular substitution, with resolution of 1.6 Å. The nPELa monomer showed an N-glycosylation site at the Asn119 residue, therefore, confirming the literature prediction. In addition, nPELa has a metal binding site and a conserved carbohydrate recognition domain, in a similar way to what was shown by other Dalbergieae tribe lectins, such as PAL (Pterocarpus angolensis) and CTL (Centrolobium tomentosum). As molecular docking analysis suggests high affinity of this lectin for different mannosides, mainly trimanosides, formed by α-1,3 or α-1,6 glycosidic bond, as evidenced by the obtained scores. In addition, molecular dynamics simulations were performed as a way of demonstrating the structural behavior of nPELa in aqueous solution, as isolated lectin or associated with specific ligands. The results demonstrated a high stability of nPELa in solution, and structural modifications presented at its carbohydrate recognition site allow the interaction between the lectin and the different ligands tested. Different modifications were observed during simulations for each one of the glycans tested, which included different number of hydrogen bonds and hydrophobic interactions, through changes in residues involved. In addition, nPELa was evaluated for its nociceptive activity in rats and was reported as a first lectin of the Dalbergieae tribe which exhibited hypernociceptive activity in a manner dependent on the carbohydrate recognition site.